Changes in sexual function and serum testosterone levels in patients with prostate cancer after image-guided proton therapy. (2nd March 2021) - Hattori, Yukiko; Iwata, Hiromitsu; Nakajima, Koichiro; Nomura, Kento; Hayashi, Kensuke; Toshito, Toshiyuki; Hashimoto, Shingo; Umemoto, Yukihiro; Mizoe, Jun-etsu; Ogino, Hiroyuki; Shibamoto, Yuta
Abstract: Since sexual function and testosterone levels after image-guided proton therapy (IGPT) have not yet been examined in detail, we prospectively evaluated changes before and after IGPT. Among patients treated with IGPT with or without combined androgen blockade (CAB) therapy between February 2013 and September 2014, patients who agreed to participate in the study and were followed up for >3 years after IGPT were evaluated. Serum testosterone levels were regularly measured together with prostate-specific antigen (PSA) levels before and after IGPT. The Erection Hardness Score (EHS) and the sexual domain summary, function subscale and bother subscale of the sexual domain in the Expanded Prostate Cancer Index Composite (EPIC) were assessed. There were 38 low-risk, 46 intermediate-risk and 43 high- or very-high-risk patients (NCCN classification). Although serum testosterone levels in low-risk patients did not decrease after IGPT, reductions were observed in the average EHS and the sexual domain summary score of the EPIC. In intermediate-, high- and very-high-risk patients, testosterone and PSA levels both increased following the termination of CAB after IGPT, and the average EHS increased. The sexual domain summary score gradually increased, but not above minimally important differences. In intermediate-risk patients, the function subscale increased from 4.4 to 14.8 ( P  < 0.05) 12 months after IGPT and reached a plateau after 60 months. The results of the present study would suggest the potential of IGPT, and further prospective studies to directly compare IGPT with other modalities are warranted.